Can the evolution of implied volatility be forecasted? Evidence from European and US implied volatility indices - Konstantinidi, Eirini; Skiadopoulos, George; Tzagkaraki, Emilia (Journal of Banking & Finance, 2008)
We address the question whether the evolution of implied volatility can be forecasted by studying a number of European and US implied volatility indices. Both point and interval forecasts are formed by alternative model specifications. The statistical and economic significance of these forecasts is examined. The latter is assessed by trading strategies in the recently inaugurated CBOE volatility futures markets. Predictable patterns are detected from a statistical point of view. However, these are not economically significant since no abnormal profits can be attained. Hence, the hypothesis that the volatility futures markets are efficient cannot be rejected.